P1173Interlead electrical delay time as early predictor of the reverse myocardial remodeling in modern CRT devices. (18th June 2020) - Lubimceva, T; Lebedeva, V; Aznauryan, R; Kamenev, A; Gureev, S; Lebedev, D
Abstract: Funding Acknowledgements: Russian Science Foundation Grant №19-14-00134 Background: Cardiac resynchronization therapy (CRT) has undoubtedly shown a high role in the treatment of advanced heart failure (HF). Despite the quadripolar left ventricle (LV) lead widespread use, the problem of low response to CRT remains actual. The search for predictors of the CRT response is an important scientific and practical task. The aim To determine the relationship between the interlead electrical delay time and the CRT response during 12 month observational period. Materials and methods: We evaluated the clinical status, the quality of life and echocardiographic response of 50 patients with HF treated for 1 year with quadripolar LV lead CRT devices implanted according to guidelines: 35 males/15 females with age 62.78 ± 11.58 years, 28 pts with history of ischemic cardiac disease, LVEF 27.42 ± 9.56%; QRS duration 157.34 ± 19.76 ms. The response to CRT was defined as 15% decrease of end-systolic left ventricle (LV) volume (LVESV), 10% relative increase of LV ejection fraction (LVEF), an improvement of at least 1 NYHA HF functional class. Interlead electrical delay time (EDT) was calculated automatically during CRT implantation, and subsequent 3-6-12 month FU. EDT values from 4 LV lead poles were evaluated according to LV sizes, volumes and LVEF. Results: It was shown that the greater EDT value, the more pronounced was response to CRT. The first difference in EDT is observed after 6-month observational period. The EDT difference was determined using the delta formula for equalize. In 21 patients in whom the stimulation of the LV lead was carried out from a pole having a maximum EDT value, the response to CRT was observed earlier - at 6 months FU (24 pts with maximum EDT value vs. other 26 pts). In addition, the echocardiographic data of reverse myocardial remodeling (LVESD, LVEDD, LVESV, LVEDV and LVEF) correlated with a gradual decrease in the EDT values, r = 0.49, P = 0.008. There were no differences between the HF etiology (ischemic/ non-ischemic) and baseline rhythm. The mean EDT was initially 104.94 ± 44.22 ms, 6 month FU 98.91 ± 34.28 ms, 12 month FU 91.84 ± 32.78 ms. Conclusion: The interlead electrical delay time in quadripolar CRT devices depends on reverse myocardial remodeling. EDT gradual decrease may be a predictor of the response to CRT.